Plant growth and diosgenin enhancement effect of silver nanoparticles in Fenugreek (Trigonella foenum-graecum L.) - B. Jasim; Roshmi Thomas; Jyothis Mathew; E.K. Radhakrishnan (Elsevier, 2017)
Various methods have been used to enhance production of chemically diverse phytochemicals especially medicinal natural products. With the advancement in nanotechnology, nanoparticles have been reported to have varying impact in plant growth and inducibility of phytochemical composition. Major objective of the study was to study the secondary metabolite modulatory effect of silver nanoparticles. In the current study, treatment of fenugreek seedlings with biosynthesized silver nanoparticles (Ag-NPs) was found to have significant impact on its growth parameters such as leaf number, root length, shoot length and wet weight. On HPLC based analysis, Ag-NPs treated seedlings showed an enhancement in the production of major phytochemical diosgenin to a level of 214.06 ± 17.07 μg/mL. An untreated control gave an yield of only 164.44 ± 7.67 μg/mL of diosgenin, and the observed phytochemical enhancement effect induced by Ag-NP was very significant. Most remarkably, the Ag-NP used in the study was found to play dual role of enhancement of both plant growth and diosgenin synthesis. Hence the study is of immense application as it opens up development of new methods based on nanoelicitors to enhance the biosynthesis of medicinal natural products in plants.